Monitoring of electrical energy quality on the traction substation input - Gryb, O.G.; Gapon, D.A.; Ierusalimova, T.S.; Borodin, D.V.; Diachenko, A.V. (Електротехніка і електромеханіка, 2015)
For the implementation of measures to maintain the quality of the energy industrial enterprises have to spend a significant material and monetary assets. In this regard, significant is the feasibility study of the allocation of such funds and, primarily, the determination of the economic damage arising from low quality of electricity. The reliability of the electricity metering system, relay protection and automation of modern digital substations depends on the quality of electrical energy. At the present time to improve the reliability of the substation operation it is necessary to monitor indicators of quality of electric energy, allowing you to take organizational and technical solutions for their improvement. Monitoring the power quality at the input traction substation has shown that indicators such as the coefficient of the n-th harmonic component of the voltage does not meet the standards GOST 13109-97. The source of higher harmonics is a voltage Converter used on the locomotive. To eliminate higher harmonics in the supply network for traction substations will need to install power filters. Today, the USB-analyzer of power quality «Digital system for the measurement of electrical energy quality» type of DSMEEQ of accuracy class 0.2. Work energy requires reliable and quality electricity supply to consumers. The new model of balancing energy market are bilateral contracts. The main task of this market, it ensure the stable and reliable operation of the unified energy system of Ukraine, that is, transmission and supply of electricity of appropriate quality.